2006
DOI: 10.1016/j.athoracsur.2005.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Results of Initial Operations in Non–Small Cell Lung Cancer Patients With Single-Level N2 Disease

Abstract: Background: There is still debate regarding the use of surgery in the management of non-small

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
2
20
1
4
Order By: Relevance
“…In particular, patients with N2 mediastinal lymph node involvement remain poor candidates for initial surgical resection even if neoplastic invasion is limited to a single mediastinal station [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, patients with N2 mediastinal lymph node involvement remain poor candidates for initial surgical resection even if neoplastic invasion is limited to a single mediastinal station [1].…”
Section: Introductionmentioning
confidence: 99%
“…Cerfolio and Bryant showed that 5-year survival of patients with unsuspected N2 disease who underwent complete resection, followed by adjuvant therapy, was 35% and patients with single station N2 disease fare better [18]. On the other hand, Ohta et al reported a 5-year survival rate of 27.1% in single level N2-disease NSCLC patients and suggested that initial operation had yet to be validated for patients with this disease [19]. Nevertheless, 5-year survival rates of non-surgery arms reported by some randomised studies range from 14% to 20% and did not exceed 30% [4,5].…”
Section: Discussionmentioning
confidence: 93%
“…Ohta ve ark. [14] tek istasyon tutulumu olan ameliyat öncesi N2 hastalık tespit edilmi ameliyat ettikleri 94 hastanın be yıllık sa¤kalımını %27.1 ve medyan sa¤kalım süre-sini 22 ay olarak saptadıklarını bildirmilerdir. Cerfolio ve Bryant'ın [15] 2008 yılında yayınladıkla-rı tesadüfi N2 hastalık serisinde tek istasyon tutulumu olan 98 hastanın iki yıllık sa¤kalımlarının %61, be yıllık sa¤kalımlarının ise %26 oldu¤u bildirilmitir.…”
Section: N2unclassified
“…[11,[14][15][16] Süperior mediastinal lenf nodlarına metastaz birçok çalımada kötü sa¤kalım ile ilikili bulunmasına karın bazı çalımalarda aksi sonuçlar elde edilmitir. [16][17][18] Çalımamızda da, süperior mediastinal lenf nodu metastazı saptanan hastalarda genel sa¤kalım oranının %22.2, hastalıksız sa¤kalım oranının %28.6 olarak bulunmasıyla en kötü sa¤kalım oranına sahip oldukları tespit edildi.…”
Section: N2unclassified